Neostigmine infusion versus syrup lactulose for the treatment of constipation in Intensive Care Unit (ICU) : a randomized, controlled study - Suhaimi, Norlida (2016)
Introduction Constipation and its implications have received very little attention even though this gastrointestinal motility disorders are common in critically ill patients. Constipation is defined as failure of the bowel to open for 3 consecutive days. This condition can give rise few adverse implications in critically ill patients such as more constipated patient failed to wean from mechanical ventilation, the median length of stay in intensive care increase and the proportion of enteral feeding intolerance were greater than non-constipated patients. Objectives To compare bowel opening between groups of patients who receive neostigmine infusion versus syrup lactulose for treatment of constipation in ICU. Methodology This is a prospective study. The ventilated patients who fulfilled the inclusion criteria and were admitted to HUSM ICU between February till October 2015 were randomly received either neostigmine infusions 0.4 – 0.8 mg/hour or syrup lactulose 15 mls TDS. Incidence of bowel opening, time to first bowel opening and any adverse reactions were recorded. Results 40 patients were randomized where 20 patients in each group either neostigmine infusion or syrup lactulose. Neostigmine infusion group significantly had bowel opening (pvalue= 0.027) and markedly had faster onset of bowel opening (p-value<0.001) compared to syrup lactulose group. There was no significant mean different in term of length of mechanical ventilation between two group of therapy (p-value=0.542). No complications occurred from the neostigmine infusion. Conclusion Neostigmine infusion was effective for treatment of constipation in ICU compared than standard therapy syrup lactulose. Continuous intravenous neostigmine infusion of up to 0.8 mg / hour to critically ill patients appears to be safe.